Residual force depression is affected by muscle length - Atsuki Fukutani; Tadao Isaka (Scientific Reports)
Abstract The isometric force attained after active shortening is smaller than that attained during purely isometric contractions, although the sarcomere length and activation level are the same. This phenomenon is known as residual force depression. This study aimed to examine whether the magnitude of residual force depression is affected by muscle length. Single-skinned fibers obtained from the rabbit psoas muscle (n = 8) were used in this study. We measured the isometric forces at an average sarcomere length of 2.1, 2.4, and 2.7 μm, and the isometric forces attained after active shortening (from 2.7 to 2.4 μm, and from 2.4 to 2.1 μm) to calculate the magnitude of residual force depression attained at both long (2.4 μm) and short (2.1 μm) length conditions. The magnitude of residual force depression was significantly larger in the long than short condition (p = 0.046). Although not statistically significant, the mean force attained during shortening was greater in the long than in the short condition (p = 0.074, note that all fibers showed larger mechanical work in the long condition). This tendency of difference in force (mechanical work attained during shortening) between the conditions is one of the reasons for muscle length-dependent residual force depression; however, some fibers showed small differences in mechanical work and large differences in residual force depression between the conditions, indicating that the magnitude of mechanical work did not simply explain the magnitude of residual force depression.